INDUCTION OF ROOT THROUGH MEDIATION OF STRAIN OF AGROBACTERIUM RHIZOGENES IN CRYSANTHEMUM - NISHA M. PATIL; S. G. BORKAR (The Bioscan, 2014)
Rooting induction in chrysanthemum cultivar Arka Suvarna through the infection of A.rhizogenes strain RPB13 was demonstrated. Without the application of IAA and IBA A.rhizogenes strain RPB13 induced rooting with increasing survival percentage (100%)along with highest no. of roots (max. 15/explants). In contrast, hormonal treated showed survival percentage 88% and no. of roots was max. 9 per explants. Hence induction of rooting in chrysanthemum micropropogated cuttings was improved following inoculation with RPB13 suggesting that this rooting treatment has opened an avenue.